Konseling Rasional Emotif Perilaku: Sebuah Tinjauan Filosofis - Bakhrudin All Habsy (Universitas Mathla'ul Anwar Banten, 2018)
RATIONAL EMOTIVE BEHAVIOR COUNSELING: A PHILOSOPHICAL REVIEW. Rational Emotive Behavior Counseling is a comprehensive, active-directive, philosophical and empirical counseling based on psychotherapy that focuses on solving problems of emotional and behavioral disorders, as well as delivering individuals to happier and fulfilling lives more lives. The foundation of the philosophy of Rational Emotive Behavior Counseling is phenomology, which implies that there is no problem within oneself, which causes one to be troubled is his or her own. Rational emotive behavior counseling is done by using a varied and systematic procedure that is specifically intended to alter behavior within the boundaries of objectives that counselors and counselees work on together. General Purpose Rational Emotive Behavior Counseling helps counselees to identify irrational belief systems and then modify them to become more rational. Rational Counseling Emotive Behavior is practiced around the world and has many counseling applications, over 50 years of existence, Rational Emotive Behavior Counseling has been successfully applied to individuals, groups, marriages, families and for a variety of issues.